Enhancing Children's Storytelling Skills Through a Picture Story Approach - Yusuf Kamaruddin, Muhammad; HF, Alkifrah Daniyal.; Lesbatta, Delkia (Journal of Islamic Education Students (JIES), 2025)
This study aims to analyze the implementation of storytelling methods supported by visual media to enhance storytelling skills in early childhood. The research was conducted at KB Aurora, Latta, Indonesia, using a classroom action research design consisting of two intervention cycles, involving 11 children aged 5ÔÇô6 years. In each session, theme-based storytelling was combined with the use of visual media to support the learning process. The results showed a significant improvement in the children's storytelling skills. Before the intervention, more than half of the participants were categorized as "Not Yet Developed," but after the intervention, 90.9% of the participants achieved the category "Developing as Expected" or higher. Visual media proved effective in enriching vocabulary, improving fluency and coherence of stories, and encouraging active participation and self-confidence in children. This study emphasizes the importance of integrating storytelling methods with visual media in the Early Childhood Education (PAUD) curriculum as a practical and effective approach to support the development of children's language skills.┬á